2021
DOI: 10.4081/qrmh.2020.9427
|View full text |Cite
|
Sign up to set email alerts
|

Living with Parkinson’s disease and connected to the duodopa pump: A qualitative study

Abstract: Parkinson’s Disease (PD) is a complex and heterogeneous disease that has a major impact on the lives of patients and their family caregivers. The duodopa pump is one of the treatments options for advanced PD. The experience of patients with this treatment is largely unexplored, however. This study is based on the experiences of patients with PD as well as their family caregivers using the pump. We take a multimodal approach that includes narrative semi-structured interviews and drawings. This methodology helps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…This study identified four groups of experiences reported by the patients and their family caregivers that can be classified in the following way: daily life and perception of PD and the effects of device-aided treatments, self-perception, social interaction and partnership/family dynamics, and experiences with different healthcare professionals including the receipt of PD diagnosis and the specific health needs of PD patients [52]. Due to the enormous amount of data obtained with this study and the different research questions we had, we decided to divide the results into three articles answering different questions [52,53]. Therefore, this article will focus on the first three categories mentioned above that are related to the experiences of PD patients treated with DBS and their FCs.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study identified four groups of experiences reported by the patients and their family caregivers that can be classified in the following way: daily life and perception of PD and the effects of device-aided treatments, self-perception, social interaction and partnership/family dynamics, and experiences with different healthcare professionals including the receipt of PD diagnosis and the specific health needs of PD patients [52]. Due to the enormous amount of data obtained with this study and the different research questions we had, we decided to divide the results into three articles answering different questions [52,53]. Therefore, this article will focus on the first three categories mentioned above that are related to the experiences of PD patients treated with DBS and their FCs.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of DIPEx is to present to a wide public (patients, family caregivers, health professionals, and students) a wide spectrum of diverse perspectives about different illnesses and health conditions [56,57]. Therefore, the Selected Material of the presented data in this paper will be uploaded to the Swiss DIPEx website in 2022 (www.dipex.ch, accessed on 4 May 2021) [53].…”
Section: Recruitment and Collaborationsmentioning
confidence: 99%
See 3 more Smart Citations